Efficient and rapid transformation of high silica CHA zeolite from FAU zeolite in the absence of water. Issue 19 (26th April 2017) - Xiong, Xin; Yuan, Dingzhong; Wu, Qinming; Chen, Fang; Meng, Xiangju; Lv, Ruihua; Dai, Daniel; Maurer, Stefan; McGuire, Robert; Feyen, Mathias; Müller, Ulrich; Zhang, Weiping; et al.
Abstract : High quality CHA zeolite catalysts were efficiently synthesized by fast transformation of FAU zeolite in the absence of water. Abstract : High silica CHA zeolite plays an important role in selective catalytic reduction of NO x with NH3 (NH3 -SCR), but its synthesis is not highly efficient due to the use of a relatively high-cost structural directing agent (SDA) N, N, N -trimethyl-adamantammonium hydroxide (TMAdaOH) and relatively long crystallization time under hydrothermal conditions. Herein, we report an efficient and rapid synthesis of a high silica CHA zeolite possessing good crystallinity and uniform crystals (CHA-ST). The method includes interzeolite transformation of high silica FAU zeolite in the absence of water but the presence of zeolite seeds and a bromide form of the SDA. The absence of water in the synthesis significantly improves the zeolite yield by avoiding dissolution of aluminosilicate species in aqueous media, while the addition of zeolite seeds remarkably enhances the crystallization rate under solvent-free conditions. In addition, this route allows the use of a low-cost bromide form of the SDA. Catalytic tests in the NH3 -SCR show that copper-exchanged CHA-ST (Cu-CHA-ST) exhibits comparable catalytic properties to those of Cu-SSZ-13 obtained from the conventional hydrothermal route.